Linkage between spruce forest decline and cloud cover increase in the Qilian Mountains of the northeastern Tibetan Plateau - Yang, Jing; Zhao, Baowei; Zheng, Jiacheng; Zhang, Qi; Li, Yan; Ma, Fuhai; Fang, Ouya (Trees (Berlin, West), 2023)
Key message The decline in Qinghai spruce forests was not aggravated by increasing temperatures; rather, excess cloud cover was the main trigger of forest decline. Forest declines accompanied by global warming have been increasingly reported worldwide. However, such declines are less frequently observed on the Tibetan Plateau. To assess the decline risk in Tibetan Plateau forests, we studied tree rings from two spruce ( Picea crassifolia ) forests in the Qilian Mountains of the northeastern Tibetan Plateau. We collected increment cores from 35 spruce trees at each sampling site in Qilian and Menyuan counties. Tree-ring widths were measured, crossdated and detrended. Growth decline in trees was identified based on low tree-ring index values lasting at least eight years. The percentage of the number of declining trees in all the samples was used to evaluate the occurrence and degree of forest decline events. The results showed that forest declines occurred at a low level during 1915–1933 and 1994–2005 in Qilian County and during 1996–2003 in Menyuan County. The radial growth of spruce had a significant negative correlation with the amount of cloud cover in the growing season. The results suggest that the growth declines of the spruce forests were not directly induced by the recent climate warming but were more likely related to stress conditions under increased cloud cover. Our findings provide insights into the assessment of forest decline risks and planning of forest protection.